IDENTIFICATION OF ALDOSTERONE E-DRIVER SOMATIC MUTATIONS IN CELL- FREE DNA FROM ADRENAL VEIN SAMPLES OF PRIMARY ALDOSTERONISM PATIENTS - Nazri, Siti Khadijah Syed Mohammed; Zakaria, Rozman; Sukor, Norlela; Azizan, Elena Aisha (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Cell-free DNA fragments (cf-DNA) of tumour cells are often found in the blood downstream to the tumour due to the high apoptosis/necrosis rate of the cells. Primary aldoste- ronism (PA), a curable cause of secondary hypertension, is commonly due to an autonomous aldosterone-producing adenoma (APA) that harbours a somatic mutation in an aldosterone-driver gene. We aimed to determine the utility of cf-DNA genotyping from adrenal vein samples (AVS) for aldosterone-driver gene mutations as a biomarker for APA. METHODOLOGY Genotyping of cf-DNA from AVS of PA patients was performed using the Agena MassARRAY platform. In this study, six samples of cf-DNA from three PA patients were interrogated. RESULTS Of the three PA patients, two had unilateral APA and one had bilateral APA. Of the six cf-DNA samples, two samples from the same patient (right adrenal and left adrenal) were found to have a mutation in an aldosterone-driver gene. Genotyping of the cf-DNA of the right AVS yielded a CTNNB1 S45P mutation whereas the cf-DNA of the left AVS had a KCNJ5 G151R mutation. CONCLUSION These results suggest that the genotyping of cf-DNA of APA from AVS samples is promising to detect the somatic muta- tions present in the APA. However, as AVS is an invasive procedure, genotyping of cf-DNA from peripheral blood may be investigated as an alternative. Therefore, further work is needed to ensure this strategy can be non-invasive as then it can be used as a screening method before AVS.